Preference Survey Of Generalized Enterprise Knowledge Portal (EKP) Versus Distributed Knowledge Management Portals (DKMPs) : A Case Study In A Software Engineering Division Of A Multinational Company In Malaysia - Teh, Sok Wei (2006)
This research focuses the preference of Enterprise Knowledge Portals (EKP) or Distributed Knowledge Management Portals (DKMPs) of the knowledge workers in the software engineering division of the multinational company located in Cyberjaya.